EVALUASI PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL CIPP PADA KEJAR PAKET B KOTA SEMARANG - Venissa Dian Mawarsari; Martyana Prihaswati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Kejar Paket B is a non-formal education which is the same to Junior High Schools. Curriculum of Kejar Paket B is also the same to a given curriculum on Junior High Schools. Although having the same curriculum, but it has different implementation of the learning process. One of these facilities in terms of the learning process, teachers often make the conventional learning.The objective  of this research is to evaluate the implementation of learning mathematics in Semarang Kejar Paket B using CIPP model (Context, Input, Process, Product). This research consists of four evaluation, namely: (1) the context evaluation, (2) the input evaluation, (3) the process evaluation, and (4) the results evaluation. This research used a qualitative approach. The results showed that the instruments used in the evaluation of the learning process using CIPP model can be used with little revision. Moreover the process of implementation of the researchindicates that the process of learning mathematics in Semarang Kejar Paket  B is not well structured from the procurement needs of students, facilities, and the teaching material of mathematics. It is also supported by the unapproriateness of acquisition results of the Final National Exam score.